Interaction of two flavonols with fat mass and obesity-associated protein investigated by fluorescence quenching and molecular docking. Issue 13 (3rd October 2018) - Wang, Zechun; Wang, Ning; Han, Xinxin; Wang, Ruiyong; Chang, Junbiao
Abstract : The binding of two flavonols with fat mass and obesity-associated protein (FTO) was studied using fluorescence spectroscopy, Stern-Volmer kinetics, UV-Vis absorption, and molecular docking. The quenching of FTO fluorescence was determined to be static with binding constants on the order of 10 4  M −1 . The interaction was studied over three temperatures, and the binding was found to be exothermic with a positive change in entropy. Thermodynamic analysis and molecular modeling suggest that hydrophobic interaction and hydrogen bonding interaction are the main binding force in stabilizing the flavonol–FTO complex.